Tinjauan Yuridis Tindak Pidana Penipuan Social Engineering pada Nasabah Perbankan melalui Aplikasi Chat Whatsapp - Nur Hidayah; Amran (PT PUSTAKA CENDEKIA GROUP, 2023)
The aims of this research are: 1) to find out the practice of social engineering fraud on banking customers via the WhatsApp chat application and 2) to find out the legal sanctions against perpetrators of criminal acts of